P041 How is the value of point-of-care tests for STIs negotiated in the context of a nationalised health system?. (14th July 2019) - Pacho, Agata; De-Allie, Emma Heming; Furegato, Martina; Harding-Esch, Emma; Tariq Sadiq, S; Fuller, Sebastian
Abstract : Background: Affordability, ease-of-use, rapid turnaround times and laboratory-equivalent accuracy have been identified as essential characteristics for point-of-care tests (POCTs) for STIs. Yet meeting these benchmarks does not guarantee POCT adoption into sexual health services (SHSs). Qualitative research can provide contextual understanding for how POCT characteristics are valued in relation to structural and political processes within health systems. Methods: We invited England SHSs interested in adopting POCTs for STIs to participate in the Facilitators to Adoption study, focused on understanding key facilitators and barriers to technology adoption within their services. Within these SHSs, we conducted in-depth interviews with key stakeholders self-identified as integral to adoption of POCTs into their services. Interviews were thematically analysed in NVIVO 11 to examine 'appropriateness' and 'usefulness' of POCT characteristics in the context of participating SHSs and the overall priorities of the National Health Service (NHS) in England. Results: 31 healthcare professions from 6 SHSs were interviewed between April and November 2018. Interviewees identified cost-effectiveness and ease-of-use as important in assessing POCTs attractiveness to their services. POCTs were seen by service leads as cost saving only if they affect costs directly incurred by the service, while potential effectiveness of POCTs was assessed by clinicians in the context of their potential for improving appropriate and timely treatment and care to area-specific priority patient groups. In some SHSs, the potential for POCTs to be seen by commissioners as increasing the competitiveness of their service by meeting new policy targets was an important factor driving adoption. Conclusion: The need for POCTs and their desirable characteristics are negotiated within complex processes of funding constraints, service restructuring and political commitments to increasing inclusivity of care. Our findings suggest that service leaders may find areas to leverage adoption of POCTs by focusing on the tests' potential to increase service relevance and competitiveness. Disclosure: No significant relationships.